Equine nasopharyngeal cryptococcoma due to Cryptococcus gattii - Cruz,Raquel Aparecida Sales da (2017)
ABSTRACT: Cryptococcus gattii is often associated with pulmonary and systemic infections in humans and animals. In this research we report a case of nasopharyngeal cryptococoma caused by C. gatti in an equine. A 10-year-old mare presented a mass obstructing the oropharynx. Macroscopically the mass was asymmetric, and was attached to the ethmoidal sinuses and obstructed the oropharynx. Histopathological examination of the mass revealed multiple yeast cells ranging from spherical to oval, 4-8μm in diameter, with some of them showing narrow base polar budding. Cryptococcus gattii growth in mycological culture (Sabouraud Dextrose Agar) and was L-canavanine-glycine-bromothymol blue Agar positive. The molecular identification confirmed the isolate as C. gattii by means of the amplification of universal primers. C. gattii is considered an emerging fungal agent, as it affects human and animals and does not respond efficiently to commonly established treatments.